Menopause symptoms versus life satisfaction and self-esteem among women - Czarnecka-Iwańczuk, Marta; Stanisławska-Kubiak, Maja; Mojs, Ewa; Wilczak, Maciej; Samborski, Włodzimierz (Menopause Review/Przegląd Menopauzalny, 2012)
Background : The symptoms of bodily changes that appear in the menopausal time cause many health and psychological problems. Moreover, they also influence the quality of life and self-esteem. Aim of the study : The aim of survey was to analyze the level of self-esteem and life satisfaction in the context of menopausal symptoms experienced by women in this period of life. Material and methods : 82 women aged 45-58 were enrolled in the study. Standardized psychological questionnaires were used. Additional data were collected using a questionnaire developed by the authors. Results : The age was negatively correlated with the score in the satisfaction with life questionnaire (Spearman’s ρ = –0.336). Hormone replacement therapy during the last 6 months’ period was associated with the results in the menopause symptom list as regards the frequency (Spearman’s ρ = –0.247) and intensity (Spearman’s ρ = –0.258) of the somatic symptoms. The score in the menopause symptom list as far as the frequency of psychological symptoms was positively correlated with the score in the self-esteem scale (Spearman’s ρ = 0.263). Moreover, the results in the scale of somatic symptoms both in frequency and intensity were negatively correlated with the results in satisfaction with life scale (Spearman’s ρ = –0.291 and –0.284). Conclusions : Older women in the menopausal period assess their life satisfaction worse. Women that experience more often and more intensive somatic symptoms of menopause, more often use hormone replacement therapy. Women with more frequent psychological symptoms of menopause have lower self-esteem. Moreover, women experiencing more frequent and intensive somatic menopausal symptoms have lower satisfaction with life.